2020
DOI: 10.1016/j.injury.2020.10.039
|View full text |Cite
|
Sign up to set email alerts
|

“Primary free-flap tibial open fracture reconstruction with the Masquelet technique” and internal fixation

Abstract: Background:Grade III open fractures of the lower extremity are serious injuries and are difficult to reconstruct. The optimal treatment for such injuries is unclear. We aimed to determine the safety and efficacy of orthoplastic reconstruction, using a primary free anterolateral thigh flap combined with the Masquelet technique and internal fixation for Gustilo grade IIIB/C open tibial fractures.Methods: From April 2018 to April 2019, 15 patients, ranging from 19 to 72 years old, with Gustilo grade IIIB/C open f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…The average union time was 13.5 months measured from the second stage of the MT to radiographic union. Kang et al revealed that the union time ranged from 4 to 7 months after the second stage of the surgery [ 20 ]. The union time was shorter than that reported by Zoller and the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The average union time was 13.5 months measured from the second stage of the MT to radiographic union. Kang et al revealed that the union time ranged from 4 to 7 months after the second stage of the surgery [ 20 ]. The union time was shorter than that reported by Zoller and the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The utility model had the advantages of fewer operations, shorter treatment cycles, rapid functional recovery, and satisfactory clinical outcomes. 43,44 We believe that the advantages of emergency microsurgical repairs are significant. First, it prevents persistent ischemic necrosis in some tissues.…”
Section: Effect Of the Time From Injury To Flap Coverage On Prognosismentioning
confidence: 99%
“…Reconstructions remain a challenge despite the availability of various technical options and bone substitutes in current surgical practice ( Balogh et al, 2012 ). Indeed, these reconstructions can be handled in different ways, depending on location, etiology, and patient’s condition, as follows: conventional techniques including autologous bone grafts ( Sun et al, 2019 ), prosthetic surgery ( Ogura et al, 2018 ; Jamshidi et al, 2020 ), peri-implant membrane induction with secondary grafting ( Masquelet and Begue, 2010 ; Giannoudis et al, 2016 ; Sivakumar et al, 2016 ), reconstructive microsurgery ( Pederson and Grome, 2019 ; Bibbo, 2021 ), distraction osteogenesis ( Lesensky and Prince, 2017 ), or a combination of these ( Niu et al, 2011 ; Houben et al, 2019 ; Kang et al, 2020 ). However, all procedures are associated with several disadvantages.…”
Section: Introductionmentioning
confidence: 99%